Fibre optic sensors for load-displacement measurements and comparisons to piezo sensor based electromechanical admittance signatures - Pang, John Hock Lye (2018)
Structural health monitoring techniques using smart materials are on rise to meet the ever ending demand due to increased construction and manufacturing activities worldwide. The civil-structural components such as slabs, beams and columns and aero-components such as wings are constantly subjected to some or the other forms of external loading. This article thus focuses on condition monitoring due to loading/unloading cycle for a simply supported aluminum beam using multiple smart materials. On the specimen, fibre optic polarimetric sensor (FOPS) and fibre Bragg grating (FBG) sensors were glued. Piezoelectric wafer active sensor (PWAS) was also bonded at the centre of the specimen. FOPS and FBG provided the global and local strain measurements respectively whereas, PWAS predicted boundary condition variations by electromechanical admittance signatures. Thus these multiple smart materials together successfully assessed the condition of structure for loading and unloading tests.